2018
DOI: 10.1002/gps.4896
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained absence resulting in deaths of nursing home residents in Australia—A 13‐year retrospective study

Abstract: Unexplained absences in elderly NH residents are a relatively common event. This study provides valuable information for aged care providers, governments, and search and rescue teams, and should contribute to debates about balancing issues of safety with independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Premature and potentially preventable deaths of nursing home residents (NHRs) have increased in the past decade (Ibrahim et al, ; Woolford, Weller, & Ibrahim, ). Unexplained absences (UA; Definition Table ) of NHRs, commonly described as “wandering,” “elopement” and “absconding” (Woolford et al, ), are recognised as contributing to mortality and morbidity rates in the nursing home (NH) population (Woolford et al, , ). The paucity of studies precludes definitive estimates of incidence and prevalence (Woolford et al, ), although a recent systematic review calculated a rate of 82 deaths and 61 injuries per 1,000 incidents of UA among community dwelling and NHRs (Woolford et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature and potentially preventable deaths of nursing home residents (NHRs) have increased in the past decade (Ibrahim et al, ; Woolford, Weller, & Ibrahim, ). Unexplained absences (UA; Definition Table ) of NHRs, commonly described as “wandering,” “elopement” and “absconding” (Woolford et al, ), are recognised as contributing to mortality and morbidity rates in the nursing home (NH) population (Woolford et al, , ). The paucity of studies precludes definitive estimates of incidence and prevalence (Woolford et al, ), although a recent systematic review calculated a rate of 82 deaths and 61 injuries per 1,000 incidents of UA among community dwelling and NHRs (Woolford et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unexplained absences (UA; Definition Table ) of NHRs, commonly described as “wandering,” “elopement” and “absconding” (Woolford et al, ), are recognised as contributing to mortality and morbidity rates in the nursing home (NH) population (Woolford et al, , ). The paucity of studies precludes definitive estimates of incidence and prevalence (Woolford et al, ), although a recent systematic review calculated a rate of 82 deaths and 61 injuries per 1,000 incidents of UA among community dwelling and NHRs (Woolford et al, ). There is considerable burden to treat injury, and to manage UAs, including the need to conduct search and rescue (SAR) operations (Cohen‐Mansfield, Werner, Marx, & Freedman, ; Furumiya & Hashimoto, ; Koester, , ).…”
Section: Introductionmentioning
confidence: 99%
“…For a wheelchair bound, person to smoke unsupervised is inher- Similar tensions also arise in situations involving unexplained absences (Woolford et al, 2018), residents who are at a high risk of falls and prefer to walk without gait aids and residents with dysphagia who wish to eat solid foods at the risk of choking. These situations all involve an element of risk which may result in harm.…”
Section: Ta B L E 2 Coroners' Recommendationsmentioning
confidence: 99%
“…We identified and extracted fourteen variables, potential risk-factors for death, based on a review of the published literature, 2,6,7,18,26,27 (Table 2). The primary outcome of this study was lost person found alive or found dead on SAR arrival.…”
Section: Data Extractionmentioning
confidence: 99%